2008
DOI: 10.1097/gme.0b013e31804d2406
|View full text |Cite
|
Sign up to set email alerts
|

Association of estrogen-related polymorphisms with age at menarche, age at final menstrual period, and stages of the menopausal transition

Abstract: Age at onset of late stage and FMP and age at menarche are associated with specific genetic polymorphisms in the estrogen biosynthesis and metabolism genes. However, because of the number of comparisons, these associations may be false positives. These findings should be confirmed with a larger sample of white women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
3
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 16 publications
2
37
3
3
Order By: Relevance
“…Of the six studies reporting continuous outcomes, only one (Stavrou et al, 2002) described a positive result, suggesting increased AAM among US women carrying the A allele and decreased AAM among those with the G allele. By contrast, the other studies examined demonstrated no significant difference between ESR1 rs9340799 genotypes in terms of AAM (Gorai et al, 2003;Xu et al, 2005;Mitchell et al, 2008;Kulik-Rechberger et al, 2010;Silva et al, 2010). Besides the small sample sizes, differences in ethnicity may be a major reason for such disagreement.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Of the six studies reporting continuous outcomes, only one (Stavrou et al, 2002) described a positive result, suggesting increased AAM among US women carrying the A allele and decreased AAM among those with the G allele. By contrast, the other studies examined demonstrated no significant difference between ESR1 rs9340799 genotypes in terms of AAM (Gorai et al, 2003;Xu et al, 2005;Mitchell et al, 2008;Kulik-Rechberger et al, 2010;Silva et al, 2010). Besides the small sample sizes, differences in ethnicity may be a major reason for such disagreement.…”
Section: Discussioncontrasting
confidence: 38%
“…Human ESR1 comprises eight exons spanning more than 300 kb of chromosome 6q25.1. A number of studies have investigated potential associations between ESR1 polymorphisms and AAM in humans (Stavrou et al, 2002;Gorai et al, 2003;Xu et al, 2005;Mitchell et al, 2008;Kulik-Rechberger et al, 2010;Silva et al, 2010). However, their results have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Semakin muda usia menarche ibu maka semakin muda pula usia menarche anak. Adanya hubungan ini diduga berkaitan dengan lokus pengatur estrogen yang diwariskan (Mitchell 2008 Tabel 6. Sebaran Subjek menurut Aktivitas Fisik subjek mengalami siklus menstruasi >35 hari.…”
Section: Menstruasiunclassified
“…Entretanto, alguns investigadores já avaliaram estes genes em relação à idade da menarca (Gorai et al, 2003;Haiman et al,1999;Mitchell et al, 2008).…”
Section: Cyp17 -Msp1aunclassified
“…Outra possibilidade seria que este polimorfismo não participasse do determinismo da puberdade. De fato, Mitchell et al (2008) estudaram 152 mulheres brancas e concluíram que o polimorfismo do CYP1B1 não está associado a idade da menarca.…”
Section: Cyp17 -Msp1aunclassified